Scene-setting and referent introduction in Turkish and Turkish sign language (Türk İşaret Dili, TİD): What does modality tell us? - Sümer, Beyza. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2015., 2015)
The aim of this thesis is to track developmental patterns setting the scene and introduce referents in narrations produced by hearing children acquiring Turkish and deaf children acquiring Turkish Sign Language (Türk İşaret Dili - TİD). Data were collected from three age groups in TİD and Turkish: younger children aged 3.5 – 6.8 years, older children aged 7.2 – 9.11 years, and adults. There were 10 participants in each group in each language. Each narrated a picture story to a deaf or a hearing person. The data were coded for linguistic elements used to set the scene (i.e., who/where/what information for the first picture) and the use of explicit linguistic forms to introduce referents (i.e., the boy, the balloon man, the balloon). TİD-signing and Turkish-speaking children reached adult patterns in scene setting elements at similar ages: In both languages, older children were similar to adults in how frequently they used different types of scene setting elements. As for referent introduction, younger children in both languages were adult-like in making explicit referrals to different referents of a story. Turkish speakers used explicit referrals to main and secondary animate and inanimate characters of the story more frequently than TİD signers, possibly an effect of modality or typological difference between the two languages.
Keywords: Sign language.; Sign language -- Turkey.